Positive Solutions for a Class of Fourth-Order p-Laplacian Boundary Value Problem Involving Integral Conditions - Yan Sun (Discrete Dynamics in Nature and Society)
Under some conditions concerning the first eigenvalues corresponding to the relevant linear operator, we obtain sharp optimal criteria for the existence of positive solutions for p-Laplacian problems with integral boundary conditions. The main methods in the paper are constructing an available integral operator and combining fixed point index theory. The interesting point of the results is that the nonlinear term contains all lower-order derivatives explicitly. Finally, we give some examples to demonstrate the main results.